2011
DOI: 10.1179/1465328111y.0000000033
|View full text |Cite
|
Sign up to set email alerts
|

Co-morbidity: exploring the clinical overlap between pneumonia and diarrhoea in a hospital in Dhaka, Bangladesh

Abstract: Increased public awareness of signs of pneumonia and severe sepsis in children under 5 is important to mitigate the risks of pneumonia and pneumonia-related deaths, and the importance of appropriate bedding for young children in reducing the risk of pneumonia needs to be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 33 publications
4
47
1
Order By: Relevance
“…13 In this study, we found that housing variables were not independently associated with pneumonia; rather, we found that broader socioeconomic indicators such as higher education status of the mother and a higher family income were protective for coinfection, which is consistent with previous studies showing that such risk factors are associated with childhood pneumonia in resource-limited settings, including Egypt, 14 Brazil, 15 and India. 16 We also demonstrate that for those under 12 months of age, breast-feeding was associated with a lower risk of concurrent pneumonia.…”
Section: Discussionsupporting
confidence: 81%
“…13 In this study, we found that housing variables were not independently associated with pneumonia; rather, we found that broader socioeconomic indicators such as higher education status of the mother and a higher family income were protective for coinfection, which is consistent with previous studies showing that such risk factors are associated with childhood pneumonia in resource-limited settings, including Egypt, 14 Brazil, 15 and India. 16 We also demonstrate that for those under 12 months of age, breast-feeding was associated with a lower risk of concurrent pneumonia.…”
Section: Discussionsupporting
confidence: 81%
“…Our isolated bacterial agents significantly differ from the common bacterial etiology of pneumonia in this age group of children [24,25]. High proportion of children with severe malnutrition (62%), a common co-morbidity of pneumonia and diarrhea in developing countries may be a factor that explains our observation- [26] -the etiology of pneumonia in under-five children is different in such children compared to those without severe malnutrition [9,27]. Our isolated bacterial agents are common in ventilation-associated pneumonia (VAP) or in nosocomial pneumonia [28,29]; however, we collected tracheal aspirates from children with community acquired pneumonia and we collected the sample immediately following their intubation and ventilation.…”
Section: Discussionmentioning
confidence: 51%
“…Several studies have examined the prevalence, health consequence, and clinical management of pneumonia however, inadequate number of literatures has reported the perception, especially of rural community mothers about pneumonia and its signs and symptoms [810]. A recent hospital based published data revealed that only 7% caregivers of pneumonic children had a good understanding and 51% had poor understanding about the clinical signs of pneumonia [11]. However, community based information is needed regarding mothers' ideas about causes of childhood pneumonia, and the healthcare seeking behaviors of mothers for their child's pneumonia.…”
Section: Introductionmentioning
confidence: 99%